An exploration of teachers' ontological and epistemological beliefs and their approaches to teaching within an IBMYP environment - Kelly, Mary C. (2013)
This dissertation uses a case study approach to investigate teachers' beliefs about the nature of reality (ontology) and knowledge (epistemology) within an International Baccalaureate Middle Years Program environment. The study explores the possible impact of these beliefs on teachers' approaches to teaching.